Playdough Media to Improve Fine Motor Skills in Early Childhood: Media Playdough untuk Meningkatkan Keterampilan Motorik Halus pada Anak Usia Dini - Jamilah, Jamilah; Ika, Mastika; Astria, Rani; Wati, Evi Sulistia; Salmia, Salmia (Universitas Muhammadiyah Sidoarjo, 2023)
General Background: Fine motor development is a crucial foundation for early childhood learning readiness, particularly for writing, drawing, and self-care activities. Specific Background: Children aged 5–6 years require appropriate stimulation to strengthen finger muscles and hand-eye coordination, yet structured motor skill programs remain limited in many kindergartens. Knowledge Gap: Although playdough has been widely used in informal learning, little research has documented its systematic application in formal early childhood education. Aims: This study investigates how structured playdough activities contribute to improving fine motor skills in children aged 5–6 years at TK Pembina Muara Sabak Barat. Results: Findings revealed significant improvements, with 80% of children demonstrating enhanced abilities in rolling, cutting, pinching, and shaping objects after four weeks of intervention. Novelty: The study highlights playdough as a low-cost, engaging, and versatile medium that integrates physical skill development with creativity and thematic learning. Implications: The results underscore the importance of incorporating sensory-based play regularly in early childhood classrooms, offering practical guidance for teachers and parents to support holistic child development. Highlights: Playdough strengthens hand-eye coordination in early childhood Structured activities improve finger dexterity and creativity Effective low-cost medium for motor and learning development Keywords: Playdough, Fine Motor Skills, Early Childhood, Sensory Play, Kindergarten